The evolutionary characteristics and driving factors of the coupling coordination degree of digital economy and cultivated land use efficiency in China - Li, Yanwei; Ma, Wenjie; Li, Yetong; Luo, Liang; Pan, Yongpeng; Wei, Jie; Cui, Yong (Frontiers in Sustainable Food Systems, 2025)
The coupled and coordinated interaction between digital economy and cultivated land use efficiency (CLUE) is of great practical significance for guaranteeing national food security. Therefore, this study constructed the evaluation index system from two aspects of digital economy and CLUE, and used the coupling coordination degree (CCD) model to measure the level of their coordination and interaction, and then analyzed the spatial and temporal evolution of the CCD. At the same time, the Tobit model is introduced to explore the driving factors and make recommendations accordingly. The study shows that: (1) Both the CLUE and the digital economy show an upward trend during the study period, but there are obvious spatial differences, and the development level of CLUE is better than that of the digital economy. (2) The CCD has steadily risen, regional differences have been narrowing, and the overall level has risen from mild disorder to benign coordination over the study period. Spatially, high value areas are mainly clustered in the eastern region and part of the central region. (3) The CCD has the stability of maintaining the original level state, and the dynamic evolution is a gradual process. There is a positive synergy effect when the level of neighboring regions is the same as its own level. (4) The Tobit model shows that economic, technical innovation and urbanization promote the CCD, while the urban–rural development gap and industrial structure inhibit the CCD.